Microbial methane cycling in a terrestrial mud volcano in eastern Taiwan - Yung‐Hsin Chang; Ting‐Wen Cheng; Wen‐Jing Lai; Wen‐Yu Tsai; Chih‐Hsien Sun; Li‐Hung Lin; Pei‐Ling Wang (Environmental Microbiology, 2012)
Summary Microbial communities responsible for methane cycling in mud volcanoes onshore are poorly characterized. This study analysed bubbling fluids and cored sediments retrieved from a mud volcano in eastern Taiwan. The pore water profiles revealed that methane concentrations generally increased with depth and changed dramatically at different depth intervals at different sites. The methane concentrations were inversely correlated with Fe 2+ /Mn 2+ concentrations and δ 13 C values of methane, marking iron/manganese‐methane transition zones in the sediment cores. Archaeal communities were dominated by ANME‐2a members and methylotrophic methanogens, whereas bacterial communities consisted primarily of Proteobacteria, Firmicutes and Bacteroidetes . The 16S rRNA gene copy numbers of ANME‐2a and Desulfuromonas / Pelobacter populations varied by two to three orders of magnitude along the profile and exhibited a pattern comparable with those of Fe 2+ and δ 13 C values of methane. These lines of evidence suggest a coupling between anaerobic methanotrophy and metal reduction in the metal‐methane transition zones under sulfate‐deficient conditions, a metabolic scheme contrasting with that observed in marine cold seeps. Anaerobic methanotrophs proliferate by removing methane produced from in situ methanogenesis and originating from the deep source. Methane finally emitted into the atmosphere is quantitatively and isotopically altered by various microbial processes compartmentalized at different depth intervals.